Instruments for measuring nursing research competence: a COSMIN-based scoping review - Yuting Xia; Hui Huang; Xirongguli Halili; Siyuan Tang; Qirong Chen (BMC, 2023)
Abstract Aim The aim of this scoping review was to evaluate and summarise the measurement properties of nursing research competence instruments and provide a summary overview of the use of nursing research competence instruments. Background Increasing nursing research competence instruments have been developed. However, a systematic review and evaluation of nursing research competence instruments is lacking. Method This scoping review was conducted following the Joanna Briggs Institute updated methodology for scoping reviews and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Reviewers searched articles in Eight English databases and two Chinese databases between April 1st, 2022, and April 30th, 2022. An updated literature search was conducted between March 1st and March 4th, 2023. The literature screening and data extraction were conducted by two reviewers, independently. A third reviewer was involved when consensus was needed. The COnsensus-based Standards for the selection of health Measurement Instruments methodology was used to evaluate the methodological quality and measurement properties of the nursing research competence instruments. Results Ten studies involving eight nursing research competence instruments were included. None of the existing instruments have assessed all measurement properties. A total of 177 empirical studies have utilized a nursing research competence instrument with tested measurement properties. Conclusion 'Self-evaluated Nursing Research Capacity of Questionnaire (refined)' was identified as the most appropriate nursing research competence instrument in existing instruments. However, reviewers need to conduct further measurement properties studies on the existing nursing research competence instruments. Implications for the nursing policy This study could guide the selection of appropriate nursing research competence instruments which could help to evaluate the nursing research competence of nurses and inform the development of intervention plans to enhance nursing research competence.